2019
DOI: 10.1097/md.0000000000018208
|View full text |Cite
|
Sign up to set email alerts
|

Nodal size ranking as a predictor of mediastinal involvement in clinical early-stage non-small cell lung cancer

Abstract: In non-small cell lung cancer (NSCLC) patients, the recommended minimum requirement for an endoscopy-based mediastinal staging procedure is sampling the largest lymph node (LN) in right and left inferior paratracheal, and subcarinal stations. We aimed to analyze the percentage of cases where the largest LN in each mediastinal station was malignant in a cohort of NSCLC patients with mediastinal metastases diagnosed in the lymphadenectomy specimen. Furthermore, we investigated the sensitivity of a preoperative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Lymph node diameter was measured in this set of images. The short-axis length of mediastinal LNs was measured at the axial plane with the largest short axis 11 . Then, a 10-mm 2 region of interest was placed on mediastinal LNs to measure the attenuation value in 16 sets of virtual monochromatic images (VMIs) (corresponding to the photon energy levels of 40 keV–190 keV at a 10 keV interval) and iodine concentration (IC) in the iodine-based material decomposition images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph node diameter was measured in this set of images. The short-axis length of mediastinal LNs was measured at the axial plane with the largest short axis 11 . Then, a 10-mm 2 region of interest was placed on mediastinal LNs to measure the attenuation value in 16 sets of virtual monochromatic images (VMIs) (corresponding to the photon energy levels of 40 keV–190 keV at a 10 keV interval) and iodine concentration (IC) in the iodine-based material decomposition images.…”
Section: Methodsmentioning
confidence: 99%
“…The short-axis length of mediastinal LNs was measured at the axial plane with the largest short axis. 11 Then, a 10-mm 2 region of interest was placed on mediastinal LNs to measure the attenuation value in 16 sets of virtual monochromatic images (VMIs) (corresponding to the photon energy levels of 40 keV-190 keV at a 10 keV interval) and iodine concentration (IC) in the iodine-based material decomposition images. The attenuation value in 40 keV to 190 keV VMIs was used to calculate the slope of the spectral attenuation curve (K) with the formula K = (HU 40keV − HU 190keV )]/(40-190) (wherein HU is the attenuation value of LN measured at single energy levels of 40 and 190 keV, respectively).…”
Section: Image Analysismentioning
confidence: 99%
“…The presence of lymph nodes whose size exceed 10 mm on the short axis should be considered a predictor of malignancy. However, results from studies focused in the accuracy of lymph node size for malignancy prediction have demonstrated that size alone is insufficient to confirm or discard metastatic infiltration of lymph nodes because of the low sensitivity (55%) reported for this technique (1)(2)(3)(4)(5)(6)(7)(8)(9)15). Additionally, the clinical relevance of nodal enlargement is limited because metastases have been found in about 20% of lymph nodes with dimensions under 1 cm on the short axis (6).…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Several authors have classified the levels of thoroughness in four categories ranging from A (optimal) to D (poorest) 34 . For surgical methods, level A is restricted to lymphadenectomy and implies complete resection of nodal stations according to the IASLC lymph node map 35 : stations 1 (low cervical, sternal notch), 2L (left upper paratracheal), 2R (right upper paratracheal), 3 (prevascular (3a)) and retrotracheal (3p)), 4R (right lower paratracheal), 4L (left lower paratracheal), 7 (subcarinal) and 8 (right (R)/left (L) paraoesophageal); and 5 (subaortic) and 6 (paraaortic) for left upper lobe tumours (Fig. 4).…”
Section: Invasive Mediastinal Stagingmentioning
confidence: 99%